2017
DOI: 10.1186/s12879-017-2547-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-dependent metabolite and cardiovascular disease marker trimethylamine-N-oxide (TMAO) is associated with monocyte activation but not platelet function in untreated HIV infection

Abstract: BackgroundHIV infection is associated with increased risk of cardiovascular disease beyond that explained by traditional risk factors. Altered gut microbiota, microbial translocation, and immune activation have been proposed as potential triggers. The microbiota-dependent metabolite trimethylamine-N-oxide (TMAO) predicts myocardial infarction (MI) in the general population and has recently been shown to induce platelet hyperreactivity. In the present study, we investigated if TMAO was associated with platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
0
19
1
Order By: Relevance
“…TMAO is converted in the liver from trimethylamine (TMA) which is an organic compound synthesized exclusively by the gut microbiota from dietary nutrients. Haissman et al [85] reported that microbiota-dependent TMAO levels are also associated with monocyte activation in untreated PLWH. By comparing PLWH with and without coronary heart disease, Kehrmann et al [86] showed that high circulating TMAO was a marker of coronary heart disease in association with the fecal abundance of Phascolarctobacterium, Desulfovibrio, Sutterella, and Faecalibacterium.…”
Section: Microbiota Gut Permeability and Inflammation In Hiv Infectionmentioning
confidence: 99%
“…TMAO is converted in the liver from trimethylamine (TMA) which is an organic compound synthesized exclusively by the gut microbiota from dietary nutrients. Haissman et al [85] reported that microbiota-dependent TMAO levels are also associated with monocyte activation in untreated PLWH. By comparing PLWH with and without coronary heart disease, Kehrmann et al [86] showed that high circulating TMAO was a marker of coronary heart disease in association with the fecal abundance of Phascolarctobacterium, Desulfovibrio, Sutterella, and Faecalibacterium.…”
Section: Microbiota Gut Permeability and Inflammation In Hiv Infectionmentioning
confidence: 99%
“…Significantly, a meta-analysis on 19 prospective studies showed that blood TMAO and its precursors are associated with elevated risk of major adverse cardiovascular events and a higher all-cause mortality independently of traditional risk factors [ 56 ▪ ]. However, a recent study in HIV infection failed to show any association between TMAO levels and platelet-hyperactivity in both treated and untreated patients [ 57 ▪ ], although TMAO levels were elevated. Rather, the study showed a significant association between TMAO and sCD14 and a higher ratio of TMAO to its precursors carnitine and betaine in treated patients.…”
Section: Microbiota and Metabolomics Studies In Hiv And Cardiovasculamentioning
confidence: 99%
“…In this last study, it was only the middle subpopulation within the second and third TMAO quartiles, compared with the first and fourth quartile, that showed an association with coronary stenosis, which suggests the involvement of other pathways. In this regard, Haissman et al [ 57 ▪ ] suggested a role for cART in TMAO metabolism. This observation together with the fact that not all patients with high TMAO levels will experience a cardiac complication limits the role of TMAO as a strong predictor of CVD.…”
Section: Microbiota and Metabolomics Studies In Hiv And Cardiovasculamentioning
confidence: 99%
“…In particular, trimethylamine-N-oxide (TMAO), a metabolite of phosphatidylcholine, was linked to plaque burden [73,74], myocardial perfusion defects [75], coronary stenosis [76] in HIV-infected subjects. Although TMAO was independently associated with microbial translocation markers (LPS) [77] and macrophage activation (sCD14, CD163) [74,77], a recent report failed to find a relationship between the metabolite and inflammation [78], suggesting its limited use as clinical marker of cardiovascular risk in HIV infection given possible confounders.…”
Section: The Metabolic Pathways Of a Dysbiotic Microbiome May Drive Imentioning
confidence: 99%